Avaliação zootécnica e econômica do cultivo de tilápia do nilo (oreochromis niloticus) sob diferentes estratégias de manejo alimentar - Freire, Marcos Vinícius de Castro (Universidade Federal Rural do Semi-Árido, 2021)
In this work, the zootechnical performance and economic viability of the production of Nile tilapia (Oreochromis niloticus), cultivated under different management strategies, were evaluated. The experimental design consisted of three treatments: cultivation system without feed and with fertilization (M1); cultivation system with feed supply and fertilization (M2); Cultivation system with feed offer and application of Calcium Sulfate (CaSO4) (M3). The zootechnical performance of the cultivated fish was evaluated, according to the average weight, the survival rate, apparent feed conversion factor, weight gain and biomass. For economic analysis, the operational cost structure and economic viability indicators were used to evaluate production. The cultivation without feed offer (M1), generated economic losses due to the low zootechnical indexes, the high production costs and negative profit, proving the importance of the feed for the adequate development of O. niloticus. The supply of feed linked to fertilization (M2), was more economically viable, since its Profitability and Profitability indices were significantly higher than the other treatments. Investing in managements that can reduce the supply of natural food (M3) can negatively influence fish survival, negatively influencing operating profit and profitability and profitability indexes during the production cycle. We conclude that semi-intensive crops of O. niloticus that use feed together with the increase of natural food in the water column of the tanks, through the fertilization of the cultivation systems, can bring economic benefits to the producer and minimize the costs with the artificial feeding
Keywords: Desempenho produtivo; Piscicultura; Rendimento econômico; Productive performance; Pisciculture; Economic yield; CIENCIAS AGRARIAS::MEDICINA VETERINARIA